Development of Comic Mathematics Learning Media Based on Contextual Approaches - Nurdin, Erdawati; Saputri, Indah Yuni; Kurniati, Annisah (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2020)
The development of teaching materials or instructional media that are tailored to the characteristics of students is considered important at this time. For this reason, this study aims to develop comic-shaped mathematics learning media based on a valid and practical contextual approach. This comic was developed based on the stages of the ADDIE development model. Based on the analysis of the data, it was concluded that this comic based contextual approach was valid and was practically used. This contextual approach-based comic can be used as an alternative learning media for material on flat side spaces.